Properties of a Finite Group Representable as the Product of Two Nilpotent Groups - Chernikov, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We establish a series of new properties of a finite group G = AB with nilpotent subgroups A and B.